PHILOSOPHICAL THOUGHT IN THE CONTEXT OF SPIRITUAL CULTURE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article examines the philosophical thought that formed the basis of the spiritual culture of the Kyrgyz people. The main stages of development of philosophical thought of thepast eras and their essence are marked.It is shown that they were not yet based on a coherent conceptual worldview, but acted in theform of philosophical ideas, tendencies and sentiments.
Keywords: culture, philosophy, thought, society, human, history, world, cognition, period.